ChemInform Abstract: Stereospecific Synthesis of γ, δ‐Diamino Esters. Issue 42 (14th October 2014) - Chin, Jik; Kwon, Soon Ho; Kim, Hyunwoo; Chin, Peter; So, Soon Mog; Kim, B. Moon
Abstract Sequential reaction of enantiopure diamine (I) with aldehydes followed by diaza‐Cope rearrangement provides γ, δ‐diimino esters in moderate to good yields and WITH excellent stereospecifity.